AGE-DEPENDING EFFICIENCY AND SAFETY OF TOPIRAMATE IN PATIENTS WITH DIFFERENT FORMS OF EPILEPSY - A. A. Kholin; N. N. Zavadenko; E. S. Il'ina; I. D. Fedonyuk; L. M. Kolpakchi; V. S. Khalilov; E. S. Kosyakova (Эпилепсия и пароксизмальные состояния)
Abstract: the aim of the study was to analyst the efficiency and safety of topiramate in children and adult epileptic populations depending on the patient’s age and forms of epilepsy. 597 epileptic patients receiving topiramate (302 males, 295 females) aged from 2 up 57 years were followed with video-EEG control during the period of 2002-2012. Topiramate was effective at 66,2% of patients (n=395). Low efficiency was seen at 26,8% (n=160) patients. The aggravation effect has been noted at 7% (n=42) of patients. Drug compliance (for >1 year) was 61,8% (n=369). High efficiency in group 2-3 year (n=134) was 53,8% (n=72), low efficiency in 34,3% (n=46), aggravation – in 11,9% cases (n=16); in group >3-7 years (n=253) high efficiency 59,7% (n=151), low 32% (n=81), aggravation in 8,3% (n=21); in pediatric population >7 years (n=132) high efficiency 81,8% (n=108), low effect in 15,2% (n=20), and 3% aggravation (n=4); in adult population >18 years (n=78) the efficiency was 82,1% (n=64), low effect 16,6% (n=13) and aggravation in 1,3% (n=1). So, topiramate is highly effective medication in the therapy of idiopathic generalized epilepsies without absences and in symptomatic/cryptogenic focal forms of epilepsy. Topiramate could also be useful additional drug in the therapy of epileptic encephalopathies. With the increasing of patients’ age the efficiency of topiramate raised, while the aggravation risks decreased. Peak of aggravation potential was seen in early childhood population and maximal effectiveness – in children up 7 years and adult population.